Daily Step Counts in Participants With and Without Peripheral Artery Disease. Issue 3 (May 2021) - Gardner, Andrew W.; Montgomery, Polly S.; Wang, Ming; Shen, Biyi; Casanegra, Ana I.; Silva-Palacios, Federico; Zhang, Shangming; Pomilla, William A.; Esponda, Omar L.; Kuroki, Marcos
Abstract : Purpose: We compared the prevalence of participants with and without symptomatic peripheral artery disease (PAD) who met the goals of attaining >7000 and 10 000 steps/d, and we determined whether PAD status was significantly associated with meeting the daily step count goals before and after adjusting for demographic variables, comorbid conditions, and cardiovascular risk factors. Methods: Participants with PAD (n = 396) and without PAD (n = 396) were assessed on their walking for 7 consecutive days with a step activity monitor. Results: The PAD group took significantly fewer steps/d than the non-PAD control group (6722 ± 3393 vs. 9475 ± 4110 steps/d; P < .001). Only 37.6% and 15.7% of the PAD group attained the goals of walking >7000 and 10 000 steps/d, respectively, whereas 67.9% and 37.4% of the control group attained these goals ( P < .001 for each goal). Having PAD was associated with a 62% lower chance of attaining 7000 steps/d than compared with the control group (OR = 0.383; 95% CI, 0.259-0.565; P < .001), and a 55% lower chance of attaining 10 000 steps/d (OR = 0.449; 95% CI, 0.282-0.709; P < .001). Significant covariates ( P < .01) included age, current smoking, diabetes, and body mass index. Conclusions: Participants with symptomatic PAD had a 29% lower daily step count compared with age- and sex-matched controls, and were less likely to attain the 7000 and 10 000 steps/d goals. Additionally, participants who were least likely to meet the 7000 and 10 000 daily step count recommendations included those who were older, currently smoked, had diabetes, and had higher body mass index. Abstract : Supplemental Digital Content is Available in the Text.Participants with peripheral artery disease had a 29% lower daily step count than controls, and were less likely to attain the 7 000 and 10 000 steps/d goals. Individuals least likely to meet the goals included those who were older, currently smoked, had diabetes, and had higher body mass index.